Desarrollo de un Modelo Guía de Asistencia Técnica para el Instituto Colombiano de Bienestar Familiar - ICBF - Castro Osorio, Paula Alejandra (Escuela Colombiana de Ingeniería Julio Garavito, 2019)
A crucial element for strengthening the skills and competences of a population is extensionism that seeks to extend (propagate or disseminate) knowledge; likewise, it is crucial for the development of innovation; For extensionism to take effect, it must articulately apply its three axes, technical assistance, technology transfer and training. Technical assistance as an axis of extension is of value great to the Instituto Colombiano de Bienestar Familiar (ICBF) "entity of the Colombian state that works for the prevention and comprehensive protection of early childhood, childhood, adolescence and the welfare of families in Colombia, giving special attention to those in conditions of threat, non-compliance or violation of their rights "(ICBF, s.f.), since it allows to strengthen the institutional management in its three levels (national, regional and zonal) and the quality of the provision of the Public Family Welfare Service, however, does not have a regulatory or regulatory framework designed specifically to provide technical assistance in a transversal manner in the Institute and to service operators or agents of the National Family Welfare System. Therefore, this research addresses the development of the technical assistance axis using the Schnarch product development methodology adapted by Vera, Castiblanco, & Cruz (2018) whose application contributes to the development of the technical assistance guidance model for the Instituto Colombiano de Bienestar Familiar in accordance with the requirements of the National Family Welfare System, the ICBF and the Integrated Planning and Management Model specifically the third dimension: Management with values by results and its policy of organizational strengthening and simplification of processes, and the sixth dimension: Management of Knowledge and innovation. The application of the Schnarch methodology was made through three phases, in the first phase the needs of the interested parties involved in the development of technical assistance in the ICBF were identified using the system dynamics methodology by means of which simulates the behavior of the technical assistance in the ICBF and allows identifying the problems that arise during its management and the respective causes. The second, through an analysis of different models of technical assistance (benchmarking), identified the characteristics and specifications that provide better results in the institutional management and the provision of the Public Family Welfare Service. Finally, in the third phase, the concept of a technical assistance model for the ICBF was elaborated and chosen.

Un elemento crucial para el fortalecimiento de habilidades y competencias de una población es el extensionismo toda vez que busca extender (propagar o difundir) conocimiento, así mismo es crucial para el desarrollo de la innovación; para que el extensionismo surta efecto, debe aplicar articuladamente sus tres ejes, la asistencia técnica, transferencia de tecnología y capacitación. La asistencia técnica como eje del extensionismo es de gran valor para el Instituto Colombiano de Bienestar Familiar (ICBF) “entidad del estado colombiano que trabaja por la prevención y protección integral de la primera infancia, la niñez, la adolescencia y el bienestar de las familias en Colombia, brindando atención especialmente a aquellos en condiciones de amenaza, inobservancia o vulneración de sus derechos” (ICBF, s.f.), ya que permite fortalecer la gestión institucional en sus tres niveles (nacional, regional y zonal) y la calidad de la prestación del Servicio Público de Bienestar Familiar, sin embargo no dispone de un marco normativo o reglamentario diseñado específicamente para brindar asistencia técnica de forma transversal en el Instituto y hacia los operadores del servicio o agentes del Sistema Nacional de Bienestar Familiar. Por lo anterior, esta investigación aborda el desarrollo del eje de asistencia técnica empleando la metodología de desarrollo de producto de Schnarch adaptada por Vera, Castiblanco, & Cruz (2018) cuya aplicación contribuye al desarrollo del modelo guía de asistencia técnica para el Instituto Colombiano de Bienestar Familiar de acuerdo con las exigencias del Sistema Nacional de Bienestar Familiar, el ICBF y el Modelo Integrado de Planeación y Gestión. La aplicación de la metodología de Schnarch se hizo mediante tres fases, en la primera fase se identificó las necesidades de las partes interesadas que intervienen en el desarrollo de la asistencia técnica en el ICBF empleando la metodología de dinámica de sistemas por medio de la cual se caracteriza el comportamiento de la asistencia técnica en el ICBF con el fin de identificar las problemáticas que surgen durante su gestión y las respectivas causas. En la segunda fase mediante un análisis de diferentes modelos de asistencia técnica (benchmarking), se identifican las características y especificaciones que proporcionan mejores resultados tanto en el desarrollo de la asistencia técnica, como en la gestión institucional y la prestación del Servicio Público de Bienestar Familiar. Finalmente, en la tercera fase se elabora y se escoge el concepto de modelo de asistencia técnica para el ICBF.
Keywords: Asistencia Técnica; Gestión del Conocimiento; Innovación; Modelo Integrado de Planeación y Gestión (MIPG); Desarrollo del producto; Dinámica de Sistemas; ISO 30401; Technical assistance; knowledge management; innovation; product development; systems dynamics; ISO 30401